Coordination, efficiency and pre-play communication with forgone costly messages - Peter H. Kriss; Andreas Blume; Roberto A. Weber (University of Zurich, Department of Economics, 2011)
We examine communication in a two-player coordination game with Pareto-ranked equilibria. Prior research demonstrates that efficient coordination is difficult without communication but obtains regularly with (mandatory) costless pre-play messages. In a laboratory experiment, we introduce two realistic features of communication by making the sending of messages optional and costly. Even small costs dramatically reduce message use, but efficient coordination of actions occurs with similar frequency to that observed under costless communication. By varying communication costs we corroborate several predictions from a theoretical analysis based on forward induction. Our results indicate that, for some levels of communication costs, explicit communication may be unnecessary for efficient coordination; instead, players simply need to know that the option to send messages was available. Thus, the relationship between communication and coordination is more complex than suggested by prior research.
Keywords: C72; C92; D83; 330; Kommunikation; Nichtkooperatives Spiel; Test